Multiview image acquisition based on an aperture sharing - Son, Jung-Young; Lee, Hyoung; Park, Min-Chul; Lee, Beom-Ryeol; Kim, Jung (THREE-DIMENSIONAL IMAGING, VISUALIZATION, AND DISPLAY 2017, 2017)
An aperture sharing camera to acquire multiview images are introduced. The camera is built with a mirrorless camera and a high speed LC shutter array which is located at the entrance pupil of the camera's objective, to divide the pupil into a number of sections with an equal dimension, The LC shutters in the array is opened one at a time in synchronizing with the camera shutter. The images from neighboring shutters reveal a constant disparity between them. The disparity between the images from the camera matches closely with that calculated from theory and is proportional to the distance of the each LC shutter from the camera's optical axis.